Rubrofusarin inhibits Aβ aggregation and ameliorates memory loss in an Aβ-induced Alzheimer's disease-like mouse model. (October 2019) - Cho, Eunbi; Cai, Mudan; Kwon, Huiyoung; Jeon, Jieun; Moon, Minho; Jun, Mira; Lee, Young Choon; Yi, Jee Hyun; Ryu, Jong Hoon; Kim, Dong Hyun
Abstract: The misfolding and aggregation of amyloid β (Aβ) peptide is a common histopathologic characteristic in patients with Alzheimer's disease, so is considered to play an critical role. In the present study, we examined the effect of rubrofusarin, an ingredient of Cassiae semen, on Aβ aggregation and memory loss in an AD mouse model. Rubrofusarin inhibited Aβ aggregation in a concentration-dependent manner. Moreover, rubrofusarin dis-aggregated preformed Aβ fibrils in a concentration-dependent manner. Although aggregated Aβ induced memory loss, Aβ pre-incubated with rubrofusarin failed to induce memory loss. Moreover, rubrofusarin administration ameliorated Aβ aggregates-induced memory loss. Finally, rubrofusarin reduced glial fibrillary acidic protein or Iba-1-positive area, markers of neuroinflammation, in the hippocampus of Aβ-treated mice. These results suggest that rubrofusarin can decrease Aβ fibril formation and ameliorate memory loss in the AD mouse model. Highlights: Rubrofusarin inhibited Aβ aggregation. Rubrofusarin dis-aggregated Aβ fibril. Aβ incubated with rubrofusarin failed to induce memory loss. Rubrofusarin ameliorated Aβ aggregate-induced memory loss.